Archetypes in the Vikings Valhalla Season 2 Movie - David Ridho Wau; Bima Prana Chitra; Hidayati Hidayati (Prodi Sastra Indonesia, FKIP Universitas Jambi, 2023)
This research examines the archetypes in The Vikings Valhalla Season 2 movie. This research aims to identify the kinds of archetypes and how archetypes related to Freydis as the main character and some supporting characters such as Queen Emma, Harald, Leif Erickson, Earl Godwin, Aelfwynn, Hrefna, Jomsvikings, and Olaf. The archetypal literary approach assumes that all humans have responses to a set of symbols, images, characters, and patterns, literary work reflects Karl Gustaf Jung. This research uses qualitative research. The data were collected by analyzing the phrases and utterances containing archetypes. Marie D. Jone's (2017) theory proposed the data analysis technique in this research. These archetypes are representations of behaviors and images that reflect the unconscious, in this research such as to survey the values of literary work in the Vikings Valhalla Season 2 movie. Abstrak Penelitian ini mengkaji arketipe dalam film Vikings Valhalla Season 2. Penelitian ini bertujuan untuk mengidentifikasi jenis-jenis arketipe dan bagaimana arketipe berhubungan dengan Freydis sebagai tokoh utama dan beberapa tokoh pendukung seperti Ratu Emma, Harald, Leif Erickson, Earl Godwin, Aelfwynn, Hrefna, Jomsvikings, dan Olaf. Pendekatan sastra pola dasar mengasumsikan bahwa semua manusia memiliki respons terhadap seperangkat simbol, gambar, karakter, dan pola, karya sastra mencerminkan Karl Gustaf Jung. Penelitian ini menggunakan penelitian kualitatif. Data dikumpulkan dengan menganalisis frasa dan ucapan yang mengandung arketipe. Teori Marie D. Jones (2017) mengajukan teknik analisis data dalam penelitian ini. Arketipe tersebut merupakan representasi dari perilaku dan gambaran yang mencerminkan ketidaksadaran, dalam penelitian ini seperti mensurvei nilai-nilai karya sastra dalam film Vikings Valhalla Season 2.